Granulocyte-colony stimulating factor-producing malignant phyllodes tumor of the breast: a rare case - Kimihisa Mizoguchi; Kazuhisa Kaneshiro; Makoto Kubo; Yoshihiko Sadakari; Yoshizo Kimura; Koichi Higaki; Toshiro Ogata; Masahiko Taniguchi (Surgical Case Reports)
Abstract Background Granulocyte-colony stimulating factor (G-CSF)-producing tumors can cause leukocytosis despite an absence of infection. G-CSF-producing tumors have been reported in various organs such as the lung, esophagus, and stomach but rarely in the breast. We report a case of G-CSF-producing malignant phyllodes tumor of the breast. Case presentation An 84-year-old woman visited our hospital complaining of a lump in her left breast without fever and pain. Laboratory tests revealed elevated white blood cell (WBC) count and G-CSF levels. A malignant tumor of the breast was diagnosed by core needle biopsy. We performed a total mastectomy and sentinel lymph node biopsy. The tumor was identified as a G-CSF-producing malignant phyllodes tumor. Within 7 days after surgery, the patient’s WBC count and G-CSF level had decreased to normal levels. She is alive without recurrence 13 months after surgery. Conclusions We encountered a rare case of G-CSF-producing malignant phyllodes tumor of the breast. PET–CT revealed diffuse accumulation of FDG in the bone. Phyllodes tumors need to be differentiated from bone metastasis, lymphoma, and leukemia. We must be careful to not mistake this type of tumor for bone marrow metastasis.